Student's Speaking Anxiety in English Foreign Language (EFL) Classroom (A Case Study in a Junior High School in Bandung) - Simatupang, Dinar (2015)
This study was conducted to investigate the level of students' speaking anxiety, the sources of students' speaking anxiety, as well as the student's strategies in overcoming language anxiety in speaking English classroom. This study employed descriptive qualitative case study. The participants of this study were 32 students in one of Junior High School in Bandung. The data were obtained from FLCAS (Foreign Language Classroom Anxiety Scale) questionnaire and interview. From 32 students which were identified, it showed that the sources of students' speaking anxiety were afraid of making mistakes (21.9%), self-perception (15.6%) , fear of negative evaluation (21.9%) and low of proficiency in English (40,6%). In overcoming their anxiety the strategies which they applied were preparation (43.75%), resignation (25%), relaxation (15.625%), positive thinking (12.5%) and peer seeking (9.375%). The findings indicate that how important the role of the teaching strategies in preventing the students from being anxious in the process of learning especially in speaking. ---------- Penelitian ini dilakukan untuk mengidentifikasi level dari kegelisahan siswa dalam berbicara bahasa Inggris, sumber-sumber yang menjadi penyebab dari kecemasan siswa dalam berbicara bahasa Inggris, serta strategi yang dilakukan oleh siswa untuk mengatasi kecemasan merak dalam berbicara bahasa Inggris di dalam ruangan kelas. Penelitian ini menggunakan metode kualitatif. Pengumpulan data diperoleh dari 32 siswa di salah satu SMP Swasta di Bandung. Data dikumpulkan dengan menggunan dua instrumen yaitu dengan menggunakan FLCAS (Foreign Language Classroom Anxiety Scale) kuesioner dan wawancara. Dari 32 siswa yang diidentifikasi, menunjukkan bahwa sumber-sumber dari kecemasan siswa dalam berbahasa inggris adalah 21.9 % takut membuat kesalahan, 15.6 % tanggapan terhadap diri sendiri, 21.9% takut dievaluasi, dan 40.6 % kemampuan dalam bahasa Inggris. Untuk mengatasi kecemasa siswa dalam berbicara bahasa Inggris, sebagian besar siswa melalukan beberapa strategi yaitu dari data yang diperoleh ada 43.75% melakukan persiapan, 25% pengunduran diri, 15.625% istirahat, 12.5% berfikir positif, 9.375% mencari teman yang mempunyai permasalah yang sama. Hasil yang diperoleh dari penelitian ini menunjukkan bahwa betapa pentingnya peran dari strategi pembelajaran untuk mencegah siswa merasa cemas di dalam proses belajar terkhusus di dalam pembelajaran berbicara dalam bahasa Inggris.